The influence of executive capacity on selective attention and subsequent processing - Daffner, Kirk R.; Tarbi, Elise C.; Haring, Anna E.; Zhuravleva, Tatyana Y.; Sun, Xue; Rentz, Dorene M.; Holcomb, Phillip J. (Frontiers in Human Neuroscience, 2012)
Recent investigations that suggest selective attention is dependent on top-down control mechanisms lead to the expectation that individuals with high executive capacity would exhibit more robust neural indices of selective attention. This prediction was tested by using event-related potentials (ERPs) to examine differences in markers of information processing across 25 subjects divided into 2 groups based on high vs. average executive capacity, as defined by neuropsychological test scores. Subjects performed an experimental task requiring selective attention to a specified color. In contrast to expectation, individuals with high and average executive capacity did not differ in the size of ERP indices of selective attention: the anterior Selection Positivity (SP) and posterior Selection Negativity (SN). However, there were substantial differences between groups in markers of subsequent processing, including the anterior N2 (a measure of attentional control) and the P3a (an index of the orienting of attention). Executive capacity predicted speed of processing at both early and late attentional stages. Individuals with lower executive capacity exhibited prolonged SN, P3a, and P3b latencies. However, the delays in carrying out selective attention operations did not account for subsequent delays in decision making, or explain excessive orienting and reduced attentional control mechanisms in response to stimuli that should have been ignored. SN latency, P3 latency, and the size of the anterior N2 made independent contributions to the variance of executive capacity. In summary, our findings suggest that current views regarding the relationship between top-down control mechanisms and selective attention may need refinement.